BIOETHANOL FROM COFFE PEEL WASTE WITH FERMENTATION PROCESS - Mohammad Yatim, Rachm, Nana Dyah Siswati, (Jurnal Teknik Kimia, 2011)
When coffee is processed, 35% of it is in the form of coffee peel waste which is a source oforganic materiali and has high levels of cellulose and is available in abundance in Indonesia, sothat can be harnessed to become bioethanol. As anlternative energy fuel, bioethanol which hashigher oxygen to content (35%) to fuel, burns moreperfectly, it also has higher octane value(118)and contains lower CO emissions 19-25%, and thus it is more environmentally friendly. Theprocess of producing bioethanol from coffee peel waste is carried out by hydrolyzing the wasteinto glucose using H2SO4 catalyst and HCl. Afterwards glucose is fermented into bioethanol usingthe bacterium Zymomonasmobilis. By implementing the variables of fermentation time, and theconcentrations of Zymomonasmobilis stater. Research shows that coffee peel can be used as analternative to produce bioethanol the process of hydrolysis and fermentation, the best resultsbeing obtained at a concentration of 11% starter and fermentation time of 7 days producebioethanol as much as 51.02% having the content 38.68% levels.Key words: Bioethanol, Fermentation, Hydrolysis, Coffee peel waste.